Meeting 21st-Century Challenges: Cultivating Critical Thinking Skills through a Computational Chemistry-Aided STEM Project-Based Learning Approach - Hulyadi Hulyadi; Faizul Bayani; Ferniawan; Sri Rahmawati; Liswijaya; Intan Kusuma Wardani; Ni Nengah Sri Swati (International Journal of Contextual Science Education, 2024)
This research aims to explore the impact of a computational chemistry-supported STEM Project-Based Learning (PjBL-STEM) application on fostering critical thinking competencies. The project focuses on green energy, utilizing waste cooking oil and aluminum to enhance students' critical thinking skills. A pre-experimental design was employed for this study, involving a sample of 22 students. Data were collected using the 21st-Century Skills Usage Scale, along with structured and semi-structured interview forms. Critical thinking was assessed through a descriptive test comprising 10 questions. The collected data were analyzed using the Wilcoxon Signed Rank Test and thematic analysis techniques. The analysis revealed a significant improvement in the students' 21st-century skills, such as autonomy, collaboration, environmental sensitivity, communication, problem-solving, creativity, responsibility, and IT literacy. Particularly notable was the students' ability to interpret structured and patterned graphical data, which they found easier to understand compared to image and narrative data. The N-gain test results indicated that the STEM-PjBL model had a positive impact on developing critical thinking abilities, with 50% of students achieving medium and high categories. Overall, the STEM-PjBL model positively influenced the development of critical thinking competencies.